FDI, exports and labor productivity of Vietnamese enterprises with different levels of capital and labor-intensity - Đào Vũ Phương Linh; Nguyễn Thị Lệ Hằng; Nguyễn Ngọc Tiến (My University, 2024)
FDI, exports and labor productivity of Vietnamese enterprises with different levels of capital and labor-intensity
Keywords: FDI and Exports; Labor productivity; Capital intensity